Filter material, method for the production of the filter material and use of melt-blown polypropylene fibers
Patent Information
- Application Number
- CN202610426943.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-03
- Filing Date
- 2026-04-02
- Publication Date
- 2026-10-16
AI Technical Summary
然而,这种过滤材料的高效率会导致压差迅速上升,同时造成过滤材料堵塞,进而产生不利地高的更换速率
[0062] The advantages, beneficial effects, and further improvements described for the filter material according to the present invention can also be applied to the method for preparing the filter material according to the present invention.
Smart Images

Figure CN122912573A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a filter material with high filtration efficiency and low pressure differential rise, as well as a method for preparing such a filter material. Similarly, this invention also relates to the application of meltblown polypropylene fibers. Background Technology
[0002] As described, for example, in WO2019 / 213107A1, air-permeable and gas-permeable filter materials are currently often equipped with nanofiber lagenae to achieve high particle separation efficiency. However, the high efficiency of such filter materials can lead to a rapid increase in pressure differential, causing clogging of the filter material and resulting in unfavorably high replacement rates. Summary of the Invention
[0003] Therefore, based on the prior art mentioned above, the technical problem to be solved by the present invention is to provide a filter material characterized on the one hand by very good filtration performance, that is, generally high efficiency and advantageously also by a high particle separation rate, and on the other hand by improved separation capacity, especially high dust storage capacity with a small increase in pressure loss, and thus resulting in extended service life and larger replacement interval.
[0004] The technical problem is solved by the features of the independent claims. The dependent claims contain advantageous further improvements and designs of the invention.
[0005] Therefore, the present invention relates to a filter material having a first layer comprising meltblown polypropylene fibers.
[0006] In the context of this invention, filter material is understood as a layered material, which is used as a filter medium, for example, after mass production, i.e., adaptive sizing, and, if necessary, layering to form a multi-layer arrangement. Filter material can also be inserted into filter cartridges and, for example, used as a replacement filter. The filter material according to the invention is particularly applicable in the field of air filters, not only in buildings but also in short-distance or long-distance passenger transport, such as buses and rail vehicles, ships, and air transport, but is not limited thereto, and can also be used as a liquid filter, such as a water filter, or as a gas filter, such as a carbon black particulate filter, or in air conditioning equipment.
[0007] For the filter material according to the invention, and more precisely for the first layer of the filter material, meltblown polypropylene fibers (hereinafter also referred to as PP fibers) are used. Meltblown PP fibers have the advantage of high mechanical and chemical stability compared to other, also plastic-based fibers. Meltblowing (also known as meltblowing) is a process that stretches an extruded polymer melt into fine fibers and establishes a uniform fiber structure through interaction with hot air. Thermoplastic fiber-forming polymers are extruded and directed into a hot (usually above 250°C) high-speed airflow as they exit the spinning nozzle. The hot, high-speed airflow typically exits near the nozzle orifice and directs the extruded polymer flow. Depending on the temperature and air volume, very fine filaments are produced through stretching. The filaments are mostly deposited on a layup tape or layup tumbler, where a fine, typically self-connected, nonwoven fiber web is created. Meltblowing differs from conventional spunbond nonwoven technology, in which the fibers are not stretched by a high-speed airflow. In other words, in conventional spunbond nonwoven fabric technology, the filaments emerging from the spinning nozzle are first cooled, appropriately stretched with the aid of air, and laid on a collection belt. This results in a significantly larger fiber diameter than the meltblown process, and the curing of the material is mostly achieved through subsequent calendering. The meltblown method is well known and described in various patents and publications, such as: NRL Report 4364, “Preparation of Superfine Organic Fibers”, by VA Wendt, EL Boone, and CD Fluharty; NRL Report 5265, “An Improved Apparatus for Forming Superfine Thermoplastic Fibers”, by KD Lawrence, RT Lukas, and JA Junge; and U.S. Patent No. 3,849,241, issued November 19, 1974, to Buntin et al. These documents are incorporated herein by reference.
[0008] The use of polypropylene has proven particularly advantageous because it is cost-effective and widely available, has a dielectric constant within a preferred range, and is therefore well electrostatically chargeable. Submicron PP fibers can be produced via a meltblown process, which can be laid on suitable substrates, optionally on a base material.
[0009] The meltblown PP fibers used in the filter material according to the invention have a fiber diameter in the range of 400 nm to 600 nm at a relative frequency (Häufigkeit) of at least 20%, for example, 20% to 60%, as determined by means of the method disclosed in the specification, and have a fiber diameter in the range of >600 nm to 800 nm at a relative frequency of at least 20%, for example, 20% to 60%, as determined by means of the method disclosed in the specification.
[0010] According to a preferred embodiment of the invention, the polypropylene fibers have a fiber diameter in the range of 400 nm to 600 nm at a relative frequency of at least 25%, for example 25% to 60%, preferably 25% to 55%, more preferably 30% to 50%, and particularly 35% to 45%, as determined by means of the methods disclosed in the specification. The determination of the relative frequency of the fiber diameter is described in the Measurement Methods and Standards section.
[0011] According to the invention, the polypropylene fibers have a fiber diameter in the range of >600 nm to 800 nm at a relative frequency of 20% to 50%, more preferably 20% to 40%, particularly 25% to 35%, as determined by means of the method disclosed in the specification.
[0012] More preferably, the polypropylene fibers have a fiber diameter in the range of 400 nm to 575 nm at a relative frequency of at least 20%, for example 20% to 60%, preferably at least 25%, for example 25% to 60%, more preferably 25% to 55%, more preferably 30% to 50%, and particularly 35% to 45%, as determined by means of the methods disclosed in the specification.
[0013] More preferably, the polypropylene fibers have a fiber diameter in the range of 625 nm to 800 nm at a relative frequency of at least 20%, for example 20% to 60%, more preferably 20% to 50%, more preferably 20% to 40%, and particularly 25% to 35%, as determined by means of the method disclosed in the specification.
[0014] In a particularly preferred embodiment, the polypropylene fibers have a fiber diameter in the range of 400 nm to 575 nm at a relative frequency of 20% to 60%, preferably at least 25%, for example 25% to 60%, more preferably 25% to 55%, more preferably 30% to 50%, particularly 35% to 45%, as determined by the methods disclosed in the specification, and have a fiber diameter in the range of 625 nm to 800 nm at a relative frequency of 20% to 50%, more preferably 20% to 40%, particularly 25% to 35%, as determined by the methods disclosed in the specification.
[0015] Preferably, compared to fiber diameters in the range of >600nm to 800nm, more preferably 625nm to 800nm, the polypropylene fibers have a fiber diameter in the range of 400nm to 600nm, more preferably 400nm to 575nm, at a higher relative frequency as determined by means of the method disclosed in the specification.
[0016] The filter material may also contain other PP fibers whose fiber diameter is not in either the range of 400 to 600 nm or >600 to 800 nm. The fiber diameter of these other PP fibers is preferably less than 5 μm, more preferably less than 4 μm, more preferably less than 3 μm, even more preferably less than 2.5 μm, and particularly less than 2 μm, in order to further improve the filtration effect of the filter material without causing a significant increase in pressure differential.
[0017] Preferably, the polypropylene fibers have a fiber diameter in the range of 700 nm to 1000 nm at a relative frequency of at least 20%, for example 20% to 60%, preferably at least 25%, for example 25% to 60%, more preferably 25% to 55%, more preferably 30% to 50%, and especially 35% to 45%, as determined by means of the methods disclosed in the specification.
[0018] More preferably, the polypropylene fibers have a fiber diameter in the range of <400 nm, preferably 10 nm to 390 nm, more preferably 50 nm to 390 nm, and even more preferably 100 nm to 390 nm, with a relative frequency of at least 15%, for example 15% to 40%, more preferably 20% to 35%, and even more preferably 20% to 30%, as determined by the method disclosed in the specification.
[0019] It has been confirmed that, as illustrated for the filter material according to the invention, the fiber diameter distribution of meltblown PP fibers results in a particularly high filtration effect and thus a very good filtration efficiency, while simultaneously extending the differential pressure rise time, thereby giving the filter material a long service life and thus allowing for large replacement intervals.
[0020] In the fiber material according to the invention, the first layer may include other fiber materials or other filter aids in addition to submicron PP fibers, for example, to separate not only particles but also other harmful substances, such as gases, bacteria or viruses.
[0021] Advantageously, due to its simplified fabrication feasibility while achieving excellent filtration performance with minimal pressure differential rise, the first layer comprises meltblown polypropylene fibers with a diameter less than 5 μm. These polypropylene fibers have a fiber diameter in the range of 400 nm to 600 nm at a relative frequency of at least 20%, for example, 20% to 60%, as determined by the method disclosed in the specification, and a fiber diameter in the range of >600 nm to 800 nm at a relative frequency of at least 20%, for example, 20% to 60%, as determined by the method disclosed in the specification. This filter material is particularly suitable for filtering particles in the air. The filter material according to the invention can be stacked in multiple layers and / or combined with other filter materials. Therefore, the filtration effect can be specifically adjusted. In a preferred embodiment, all meltblown polypropylene fibers have a fiber diameter of less than 5 μm.
[0022] According to another advantageous further improvement, the first layer has a concentration of 5 to 20 g / m³. 2 And especially 6 to 15 g / m 2 The weight per unit area within the specified range. This weight per unit area is measured using EN 29073-1:1992. Considering the improvement in filtration efficiency, it is between 5 and 20 g / m². 2 The weight per unit area within the specified range has been shown to be advantageous, and the filtration effect can be further improved by shifting the weight per unit area towards higher values. However, from values greater than 15 g / m²... 2 The weight per unit area, especially greater than 20 g / m² 2 Starting with the unit area weight, a slight increase in pressure differential may occur, when the unit area weight is limited to a maximum of 15 g / m². 2 This can be particularly effective in preventing such pressure differential increases.
[0023] To improve the separation or adsorption rate of particles through the filter material and thus further improve filtration performance, the first layer preferably has a layer thickness in the range of 10 μm to 200 μm, particularly 20 μm to 150 μm, and especially 40 μm to 80 μm. The layer thickness is determined according to DIN EN ISO 9073-2:1996, wherein the fiber sheet composed of submicron meltblown PP fibers has a thickness of 10 cm. 2 An area A and a punch force of 12.5 cN are applied, with the thickness measured in mm in the compressed region. A greater layer thickness results in higher filtration efficiency and, consequently, a higher adsorption rate of the filter. However, the cost of the filter material also increases. Considering these trade-offs, a first layer thickness in the range of 40 μm to 80 μm has proven particularly advantageous.
[0024] Furthermore, it is advantageous that the filter material includes a first substrate, wherein a first layer is disposed on the first substrate, and wherein, in particular, meltblown PP fibers are deposited on the first substrate. Using the first substrate has the advantage that the filter material is additionally mechanically stabilized. If the filter material is stored or transported, the first substrate also protects the PP fibers from contamination. This substrate has proven particularly advantageous for laying meltblown PP fibers because they can be deposited directly in layers on the substrate, thereby avoiding multiple re-laminations of the PP fibers. In a preferred embodiment, the first layer and the first substrate are interconnected by calendering. This improves the adhesion between the two layers.
[0025] To improve filtration efficiency, the first substrate is advantageously selected from at least one of spunbond nonwoven fabric, wet-laid nonwoven fabric, short-fiber nonwoven fabric, loose-laid fabric, knitted fabric, woven fabric, woven fabric, and combinations thereof. The aforementioned structure possesses a certain degree of porosity, allowing particles to pass through for deposition by the first layer.
[0026] Furthermore, given the advantageous balance between high filtration efficiency and low pressure drop, the first substrate's area weight is 8 g / m². 2 Up to 35g / m 2 Within the range and preferably between 10 and 25 g / m 2 Within the range and especially in the range of 10 to 20 g / m 2 Within this range. The weight per unit area is determined as described above for the first layer. If the weight per unit area of the first substrate is between 8 and 35 g / cm³. 2 Within this range, the filtration performance will not be adversely affected. Furthermore, the concentration of the first substrate within the range of 10 to 25 g / m³... 2 The unit area weight within the range improves the mechanical stability of the filter material and is particularly effective in preventing contamination and damage to the first layer during storage and transportation.
[0027] To further improve mechanical stability, the first substrate preferably has a layer thickness in the range of 50 to 400 μm, more preferably in the range of 100 to 300 μm, and particularly in the range of 200 to 300 μm. Here, the layer thickness is measured as described for the layer thickness of the first layer. The higher the layer thickness of the first substrate, the higher the stability of the filter material. However, a high layer thickness of the first substrate also has the disadvantage of adding additional weight and volume to the filter material, thus the layer thickness of the first substrate is advantageously in the range of 100 to 300 μm, and particularly in the range of 200 to 300 μm. This does not significantly increase the pressure drop rise.
[0028] Particularly preferably, the composite material consisting of the first substrate and the first layer has a layer thickness in the range of 50 to 400 μm, more preferably in the range of 100 to 300 μm, and particularly in the range of 200 to 300 μm. Here, the layer thickness is measured as described for the layer thickness of the first layer.
[0029] To optimize the adhesion between the first substrate and the first layer, the material of the first substrate is preferably a polyolefin, particularly polypropylene (PP). Here, the PP does not necessarily have to be the same as the PP used in meltblown PP fibers, but it particularly has a melting range similar to that of meltblown PP fibers.
[0030] Filter materials comprising at least one first layer and a first substrate as described above are well suited as filter media for filtering particles, for example, from air or also from liquids, but particularly from air. All conventionally present airborne dust particles, such as flower dust, pollen, carbon black, and cigarette smoke, can be removed from the air using the filter material according to the invention, wherein the dust particles accumulate on a filter mesh made of meltblown PP fibers.
[0031] In order to improve operation and design applications as comprehensively as possible, in addition to achieving very good filtration efficiency under small pressure rise, the filter material preferably has a layer thickness in the range of 60 to 600 μm, more preferably in the range of 100 to 400 μm, and especially in the range of 200 to 300 μm, as measured as the layer thickness of the first layer.
[0032] Furthermore, for a better balance between filter effectiveness and minimizing differential pressure rise, the filter material has a strength of 10 to 50 g / m³. 2 Within the range and especially between 15 and 40 g / m 2 The weight per unit area within the specified range. This weight per unit area is measured using EN 29073-1:1992.
[0033] According to another preferred embodiment, the filter material has a density of 400 to 500 l / m². 2 • Air permeability. This air permeability is measured according to DIN EN ISO 9237:1995, where the measurement pressure is 200 Pa and the measurement surface is 20 cm. 2 If the filter's air permeability is between 400 and 500 l / m 2 Within the range of ·s, the filter material has a high throughput rate and can filter a high volume of air in a short time. This is particularly advantageous when the filter material is used in areas with relatively large volumes of space.
[0034] To improve filtration efficiency, the filter material also advantageously includes activated carbon. Activated carbon is not specifically limited, but is preferably obtained from renewable raw materials, and particularly from coconut shells. In particular, activated carbon made from coconut shells has proven advantageous due to its high hardness and therefore good resistance, and furthermore, it exhibits particularly good adsorption capacity for n-butane, a component of engine gasoline. Because activated carbon has a large active surface area, the filter material containing activated carbon according to the invention is also preferred, especially when the medium to be filtered contains a large number of particles or gases to be filtered out, and when the particles have a very small particle diameter. Particularly advantageously, activated carbon is used for gas separation according to an advantageous further improvement.
[0035] Preferably, the filter material has a second layer comprising activated carbon. The second layer is preferably disposed on the first layer. This results in a layer sequence: first substrate / first layer / second layer. By incorporating activated carbon in the form of a second layer, filter characteristics can be more specifically adjusted because factors such as layer thickness, weight per unit area, and permeability can be adjusted independently of each other. Therefore, the filter material can be configured for its specific application through the layer composition.
[0036] The second layer can, for example, be deposited directly on the first layer. However, advantageously, the filter material includes a second substrate on which the second layer is disposed. Thus, the activated carbon filter can be manufactured and sold separately. Depending on the type of connection between the second and first layers, the corresponding layers can also be replaced as needed, for example, when maximum adsorption capacity is reached. A further advantageous improvement yields a layer arrangement having: first substrate / first layer / second layer / second substrate.
[0037] The first and second layers can be connected to each other, for example, by lamination or bonding, and may include possible auxiliary materials if necessary for this purpose.
[0038] The second substrate can be constructed in the same manner as the first substrate. In particular, the second substrate is selected from at least one spunbond nonwoven fabric, wet-laid nonwoven fabric, staple fiber nonwoven fabric, loose-laid fabric, knitted fabric, woven fabric, braided fabric, and combinations thereof.
[0039] Due to their excellent mechanical and chemical stability, the material of the second substrate is preferably a polyolefin, and in particular polypropylene.
[0040] To improve rather than impair the filtration effect, the second substrate preferably has a concentration of 20 to 100 g / m³. 2 And especially 40 to 80 g / m 2 The weight per unit area within the specified range. This weight per unit area is measured using EN 29073-1:1992. If the weight per unit area is particularly low, preferably 40 g / m², this is acceptable. 2 Furthermore, it is more preferably 20g / m2 The key advantage of filter materials is improved airflow when used as air or gas filters. This is especially true for materials with a strength greater than 80 g / m³. 2 or even greater than 100g / m 2 A higher weight per unit area may be disadvantageous in terms of the filter's "Zusetzen" (i.e., rapid attainment of maximum adsorption capacity). For the reasons mentioned above, the weight per unit area of the second substrate is 40 to 80 g / m². 2 It is particularly advantageous.
[0041] The thickness of the second substrate layer is generally unrestricted, but is preferably in the range of 200 to 800 μm, and more advantageously in the range of 450 to 600 μm, due to the mechanical stability of the filter material. For different applications requiring smaller filter materials, very high layer thicknesses exceeding 600 μm or even 800 μm may be disadvantageous. This layer thickness is measured in the same manner as the layer thickness of the first substrate and can be referred to the methods detailed above.
[0042] Furthermore, the second substrate has an efficiency of 1500 to 6000 l / m², which is advantageous for high filtration efficiency, i.e., large throughput. 2 •s, preferably 2000 to 4500 l / m 2 The air permeability is measured in ·s. This air permeability is determined using DIN EN ISO 9237:1995, where 100 Pa is used as the measuring pressure and 20 cm⁻¹ is used. 2 As the area to be measured.
[0043] To further improve the adsorption capacity of the filter material according to the invention, according to another advantageous further improvement, the activated carbon has a sieve pore size of 20×50 mesh to 60×150 mesh, particularly 30×60 mesh to 60×120 mesh. Activated carbon is particularly suitable for adsorbing n-butane, used as a probe gas in automotive environments, if the particle size is within one of the ranges given above.
[0044] The filtration efficiency can be further advantageously improved by including a hot melt adhesive bonding line in the second layer. Preferably, the hot melt adhesive bonding line (4) and activated carbon are applied together to the second substrate. The hot melt adhesive suitable for this invention is a thermoplastic material having a softening point of 115 to 170°C, and particularly 120 to 165°C. The softening point is measured according to DIN 51920 (1984 edition), in which a lead ball is placed on the adhesive surface, the lead ball pressing the adhesive through an inner joint. The lead ball has a mass of 3.2 + / - 0.2 g (diameter 32) and the inner joint has a 6.35 mm bore for receiving molten hot melt adhesive. Furthermore, the hot melt adhesive suitable for this invention has adhesive properties at the operating temperature when the filter material is used as specified. The hot melt adhesive bonding line can not only additionally, particularly, bond coarser particles, but also protect and fix the activated carbon layer, i.e., the second layer. The hot melt adhesive bonding line is advantageously present in the form of an adhesive mesh with a sticky surface. This adhesive mesh, also known as a mesh adhesive layer, is part of the second layer and allows for additional deposition of the material to be filtered due to its adhesiveness. For example, the surface tack of the hot melt adhesive can be improved by selectively adding tackifiers.
[0045] Preferably, the hot melt adhesive bonding line is a polyolefin-based hot melt adhesive bonding line, particularly an amorphous polyalphaolefin-based hot melt adhesive bonding line. More preferably, the hot melt adhesive bonding line has a diameter of 5 to 60 μm, preferably 20 to 40 μm. Particularly preferred are propylene-based polyalphaolefin-based hot melt adhesive bonding lines. The hot melt adhesive bonding line advantageously, particularly, accumulates and filters out coarser dust particles, thereby protecting the subsequent layers.
[0046] A further improvement to this advantageous design yields a layer arrangement comprising: a first substrate / a first layer / a second layer containing hot melt adhesive bonding lines / a second substrate. The filter material constructed in this way exhibits very high filtration capacity, particularly for particles of all sizes filtered through the various layers. For this purpose, the filter material preferably has a layer thickness in the range of 500 to 2500 μm, more preferably 800 to 2000 μm, and particularly 1500 to 1800 μm, wherein this layer thickness is determined using a dial gauge (Mitutoyo 543-271B) with a measurement range up to 12.7 mm, a resolution of 0.01 mm, a measuring force of 1.5 N, a punch diameter of 12 mm, and a support area of 113.1 mm². 2 The weight of the punch is 15g.
[0047] Preferably, this filter material has a strength of 250 to 500 g / m³ as measured by EN 29073-1:1992. 2 Within the range and especially in the range of 300 to 400 g / m 2The weight per unit area is within a certain range. Therefore, with very high filtration efficiency, the pressure rise can be minimized, and the filter material can be used in almost all applications, especially air purification.
[0048] Another advantageous further improvement is characterized by the filter material having a density of 100 to 150 l / m 2 The air permeability is ·s. This maximizes the filtration capacity, i.e., the volume of the filter medium passing through, while achieving very high filtration efficiency. The air permeability of the filter material is measured as described in DIN EN ISO 9237:1995, using a measurement pressure of 200 Pa and a 20 cm² depth. 2 The measured area.
[0049] Furthermore, the filter material can advantageously include an electret pre-filter. This can improve the initial filtration efficiency. The electret pre-filter can be connected to a first or second substrate, particularly by lamination, bonding, or, for example, ultrasonic welding. According to the invention, the electret pre-filter is understood as a filter layer electrostatically charged, for example, by means of corona or high-voltage technology. This further improves dust storage capacity.
[0050] Furthermore, the present invention also describes air filters (also understood herein as gas filters, such as exhaust gas filters), water filters, or particulate filters comprising the filter materials disclosed above. Air filters, water filters, or particulate filters constructed in this way are characterized by high particle separation rates while maintaining a long service life, and therefore have large replacement intervals due to a smaller pressure differential rise, based on the use of the filter materials of the present invention.
[0051] Furthermore, a method for preparing a filter material is also described according to the present invention. This filter material can be the filter material described above. In other words, the method according to the present invention can be used to prepare the filter material according to the present invention.
[0052] The method first includes the step of preparing a polypropylene melt, wherein the polypropylene used for the polypropylene melt has a melt flow rate (MFR) of 800 to 4000 g / 10 min, particularly 1100 to 2800 g / 10 min. Therefore, a low-viscosity polypropylene is involved. It goes without saying that one or two or more polypropylenes can be used, which may differ, for example, in their stereoregularity, molecular weight, or polydispersity. It is advantageous that when two or more polypropylene types are used in combination, the melt flow rate of each individual polypropylene type is in the range of 800 to 4000 g / 10 min. The melt flow rate (MFR) is measured here by means of ISO 1133-1 (2022). The melting of the polypropylene used to prepare the polypropylene melt is carried out, particularly at a temperature of 200-300 °C. This is advantageous because the melt is thus finer and can be better drawn.
[0053] Polypropylene melt can be used directly as a meltblown mixture for meltblowing. However, preferably, at least one sterically hindered hydroxylamine ester is incorporated into and mixed with the polypropylene melt to prepare a meltblown mixture containing hydroxylamine ester. Here, the content of the sterically hindered hydroxylamine ester in the melt spinning solution is preferably 0.1 to 5% by mass, more preferably 0.1 to 3% by mass, and particularly in the range of 0.1 to 2.5% by mass, based on the total weight of the meltblown mixture. Different suitable sterically hindered hydroxylamine esters are commercially available and are preferably supplied in the form of mixtures with one or more polymers. Irgatec® CR 25 or Irgatec® CR 76 from BASF can be used as examples.
[0054] The meltblown mixture is then meltblown, and the resulting polypropylene fibers are stretched with air at a temperature of at least 240°C (measured at the nozzle), for example, 240°C to 300°C, and then laid on a first substrate to prepare a polypropylene filter sheet.
[0055] Meltblowing yields meltblown PP fibers, wherein the polypropylene fibers have a fiber diameter in the range of 400 nm to 600 nm at a relative frequency of at least 20%, for example 20% to 60%, preferably at least 25%, for example 25% to 60%, more preferably 25% to 55%, more preferably 30% to 50%, particularly 35% to 45%, as determined by the method disclosed in the specification, and have a fiber diameter in the range of >600 nm to 800 nm at a relative frequency of at least 20%, preferably 20% to 60%, more preferably 20% to 50%, more preferably 20% to 40%, particularly 25% to 35%, as determined by the method disclosed in the specification. Here, the diameter of the PP fibers can be adjusted by the melt flow rate (MFR) of the polypropylene and by the content of at least one sterically hindered hydroxylamine ester used to prepare the spinning melt. The temperature of the air used for stretching is at least 240°C (measured at the nozzle), for example 240°C to 300°C.
[0056] Meltblowing of PP fibers can be carried out, for example, on a meltblowing machine, while adhering to the following parameters:
[0057] Nozzle temperature 275℃
[0058] Primary air temperature 280°C
[0059] Primary air volume 1000m 3 / hxm (nozzle length per hour and per meter)
[0060] DCD (Distance between the head and receiver) 300mm
[0061] This method can be implemented simply and without high technical costs, and can be used to prepare filter materials with high filtration efficiency, good filtration capacity and very small pressure drop.
[0062] The advantages, beneficial effects, and further improvements described for the filter material according to the present invention can also be applied to the method for preparing the filter material according to the present invention.
[0063] According to an advantageous further improvement, the method according to the invention further includes the step of preparing an activated carbon filter sheet, wherein activated carbon is first applied to a second substrate and then hot melt adhesive lines are deposited on the activated carbon.
[0064] Furthermore, the activated carbon filter sheet is connected to the polypropylene filter sheet, resulting in the following layer arrangement: second substrate / activated carbon filter sheet containing hot melt adhesive bonding lines (second layer) / / polypropylene filter sheet (first layer) / first substrate.
[0065] This advantageous further improvement scheme can further enhance filtration performance because activated carbon can introduce additional adsorption volume with a higher adsorption surface area into the filter material and can also filter out gases such as butane.
[0066] Furthermore, the present invention also describes the application of meltblown polypropylene fiber as a filter material sheet, wherein the polypropylene fiber has a fiber diameter in the range of 400 nm to 600 nm at a relative frequency of at least 20%, for example 20% to 60%, preferably at least 25%, for example 25% to 60%, more preferably 25% to 55%, more preferably 30% to 50%, particularly 35% to 45%, as determined by the method disclosed in the specification, and has a fiber diameter in the range of >600 nm to 800 nm at a relative frequency of at least 20%, preferably 20% to 60%, more preferably 20% to 50%, more preferably 20% to 40%, particularly 25% to 35%, as determined by the method disclosed in the specification.
[0067] In the above applications, it is further advantageous that the filter material sheets have a strength of 5 to 20 g / m³ as measured by means of EN 29073-1:1992. 2 Within the range, especially 6 to 15 g / m 2 Weight per unit area within the specified range. Attached Figure Description
[0068] Other details, advantages, and features of the invention will become apparent from the following description of embodiments with reference to the accompanying drawings. In the drawings:
[0069] Figure 1 A cross-section of the filter material according to the first embodiment is shown.
[0070] Figure 2 A graph illustrating the efficiency of a second embodiment of the filter material relative to the particle size of the particles to be filtered is shown.
[0071] Figure 3 The graph illustrates the dust trapping capacity after a pressure drop increase of 100 Pa.
[0072] Figure 4 A REM photograph showing a top view of the filter material. Detailed Implementation
[0073] exist Figures 1 to 3 Only the main elements and components according to the advantageous aspects of the invention are shown. For clarity, all other elements and components are omitted. Furthermore, the same reference numerals denote the same components, elements, or parts.
[0074] Figure 1A filter material 10 according to an advantageous embodiment is shown in detail. The filter material 10 is shown in cross-section and has the following layer arrangement: a first substrate 1, a first layer 2, a second layer 3, and a second substrate 5.
[0075] The first substrate 1 is preferably a material with a weight per unit area of 10 to 20 g / m², as measured by EN 29073-1:1992. 2 The spunbond nonwoven fabric is composed of polypropylene. It has a layer thickness in the range of 200 to 300 μm, wherein the layer thickness is measured by loading the spunbond nonwoven fabric with a punch of area A of 10 square centimeters and a force of 12.5 cN, and reading the thickness measurement in mm (hereinafter: ITM = internal measurement method according to DIN EN ISO 9073-2:1996). The fiber diameter of the first substrate is advantageously in the range of 20 to 30 μm.
[0076] The first layer 2 is formed of meltblown polypropylene fibers, wherein the polypropylene fibers have a fiber diameter in the range of 400 nm to 600 nm at at least 20% of the relative frequencies as determined by the method disclosed in the specification, and have a fiber diameter in the range of >600 nm to 800 nm at at least 20% of the relative frequencies as determined by the method disclosed in the specification. The fiber diameter is determined by means of REM photographs (magnified 2000 times) as described in the measurement methods section. High filtration capacity is achieved with low pressure drop through the submicron PP fibers having a specific fiber diameter distribution, thus the filter material 10 is characterized by persistently very high adsorption properties and therefore large replacement intervals.
[0077] Because the same chemical materials are used, there is a high degree of adhesion between the PP fibers in the first layer 2 and the first substrate 1. Furthermore, the PP fibers are deposited directly onto the first substrate 1 via melt spinning, resulting in a better layered composite.
[0078] The next layer is the second layer, or the third layer, an activated carbon layer or an activated carbon sheet containing activated carbon. Because activated carbon has a large adsorption surface area, it improves the adsorption rate, especially for particles and gases with small particle sizes.
[0079] In addition to activated carbon, the second layer 3 comprises a mesh of hot melt adhesive threads formed of PP with a melting range of approximately 110°C. The hot melt adhesive threads are deposited directly onto the activated carbon in the second layer 3, thus fixing and protecting the activated carbon. Due to their adhesiveness, the hot melt adhesive threads 4 can filter out particles with large diameters. The activated carbon and the layer composed of the hot melt adhesive threads 4 form a common heterogeneous layer, namely the unit (second layer 3).
[0080] Reference numeral 5 indicates the second substrate, which can be constructed in the same manner as the first substrate 1 and is particularly also formed of PP. It serves as a carrier for the activated carbon and contributes to the mechanical protection of the filter material 10, and is constructed in such a way, in terms of its area weight, layer thickness, and air permeability, that the filtration efficiency is not compromised and no pressure differential increase is introduced in this respect.
[0081] Figure 2 It is a graph illustrating the relationship between the efficiency of the second embodiment of the filter material and the particle size of the particles to be filtered.
[0082] The filter material is prepared as follows:
[0083] First, a polymer melt was prepared by melting metallocene-catalyzed PP (MFR 1800 g / 10 min, according to ISO 1133-1, at 230 °C). Then, Irgatec® CR 25 (manufacturer: BASF) as a sterically hindered hydroxylamine ester was continuously added to the PP matrix, such that the content of the sterically hindered hydroxylamine ester in the meltblown mixture was in the range of 0.1% by mass to 2.5% by mass relative to the total weight of the meltblown solution. The PP matrix did not affect the determination of the hydroxylamine ester content.
[0084] Processing is carried out at 250°C. This means that the meltblown mixture formed from PP and Irgatec CR®25 is spun at approximately 250°C and spun into a substrate having a unit area weight of 15 g / m². 2 On PP spunbond nonwoven fabric, the fibers are additionally stretched during spinning with the help of hot air (approximately 280°C = primary air temperature).
[0085] For this purpose, meltblown equipment is used, wherein the following parameters are observed:
[0086] Nozzle temperature 275℃
[0087] Primary air temperature 280℃
[0088] Primary air volume: 1000 m³ / h x m (per hour and per meter nozzle length)
[0089] DCD (Distance between the head and receiver) 300mm
[0090] PP spunbond nonwoven fabric has such as targeting Figure 1 The first substrate in the process was measured to have a layer thickness of 0.20 mm. The resulting double-layer laminate has a layer thickness of 0.26 mm and a g / m³ of 25 g / m³. 2 The weight per unit area (measured using EN 29073-1:1992) and 450 l / m 2•s is measured at 200 Pa and 20 cm using DIN EN ISO 9237:1995. 2 The air permeability was measured in the case of a measured area. The two material layers were calendered to obtain improved adhesion.
[0091] Therefore, the thickness of the meltblown PP fiber layer (polypropylene filter sheet) is 0.06 mm, and the fiber diameter of the obtained individual filaments is determined as described in the measurement methods section. It has been found that all fibers have a fiber diameter of less than 5 μm, and these fibers have a fiber diameter in the range of 400 nm to 600 nm at at least 20% of the relative frequencies determined by the methods disclosed in the specification, and a fiber diameter in the range of >600 nm to 800 nm at at least 20% of the relative frequencies determined by the methods disclosed in the specification.
[0092] In the second processing step, an activated carbon filter sheet is prepared using the aforementioned polypropylene filter sheet as a covering material. The second substrate used is PP spunbond nonwoven fabric with a density of 60 g / m². 2 The unit area weight, layer thickness of 0.45 mm, and the measurement pressure of 100 Pa and the measurement area of 20 cm². 2 Under the condition of 2650 (100 Pa) l / m measured with the aid of DIN EN ISO 9237:1995 2 The PP spunbond nonwoven fabric has a breathability of 230 g / m². 2 It consists of activated carbon (30×60 mesh, coconut shell base) and PP hot melt adhesive filaments (Jowatherm 238.75) and is equipped with the above two covering materials. The diameter of the hot melt adhesive filaments is 10 to 20 μm.
[0093] The obtained activated carbon laminate has the following technical data: 370 g / m³ as measured by EN 29073-1:1992. 2 The unit area weight, layer thickness of 1.60 mm, and the measurement pressure of 100 Pa and the measurement area of 20 cm². 2 130 l / m measured using DIN EN ISO 9237:1995 2 •s breathability.
[0094] A similarly constructed activated carbon laminate was used as a reference, which has commercially available nanofiber media (with 30 g / m³). 2 The unit area weight of polyester spunbond nonwoven fabric substrate, PVDF nanofibers (fiber diameter less than 100nm) and 30g / m 2(polyester covering per unit area weight), which has 60 g / m 2 The total weight per unit area and the layer thickness of 0.22 mm measured using ITM, and the measurement pressure of 200 Pa and the measurement area of 20 cm². 2 425 l / m measured using DIN EN ISO 9237:1995 2 •s breathability.
[0095] DIN 71460-1 2006 (Road vehicles—Air filters for motor vehicle interiors—Part 1: Test methods for particulate filtration) describes instrument requirements and test methods applicable to studies on filtration technology (separation efficiency = efficiency based on particle size and dust storage capacity), supplemented by DIN 71460-3 2020-10 (Road vehicles—Air filters for motor vehicle interiors—Part 3: Test of filtration efficiency eff(PMx) based on PMx), referring to the use of DEHS aerosols. For this purpose, studies are conducted using DEHS aerosols. The SAE fine dust used for dust loading tests is similar to the fine test dust described in A.2 of ISO 12103-1:2016(E).
[0096] exist Figure 2 Four curves are shown. Ref. new is a commercial nanofiber filter material used as a reference, and AF570 new corresponds to the filter material according to the present invention, the preparation method of which has been described at the beginning. Figure 2 Description. The corresponding curve labeled "IPA" is obtained after discharging (Entladung) the corresponding filter with isopropanol. Figure 2 The filter material according to the invention exhibits higher efficiency across all particle size ranges.
[0097] Figure 3 This is a graph showing the dust retention capacity of a reference filter material (Ref.) and a filter material according to the present invention (AF570) after a pressure loss increase of 100 Pa. Figure 3 The dust retention capacity of the filter material according to the present invention is shown in detail to be several times higher than that of the reference filter material after the pressure loss increases.
[0098] Figure 4 A REM photograph showing a top view of the filter material is presented. The relative frequencies of the polypropylene fiber diameters were determined using the methods described in the Measurement Methods and Standards section. The following results were obtained:
[0099] 400nm to 600nm = 34%
[0100] 600nm to 800nm = 24%
[0101] Other = 42%
[0102] In addition to the foregoing written description of the invention, reference is made hereto to the accompanying drawings for the purpose of supplementing the disclosure thereof.
[0103] Measurement methods and standards
[0104] The relative frequency of the fiber diameter of polypropylene fibers
[0105] According to the present invention, the relative frequency of the fiber diameter of the polypropylene fibers is determined as follows. A top view of the DINA4 pattern of the filter material according to the present invention is observed. If the first layer is covered by an outer layer, for example due to a covering or a first substrate disposed thereon, the first layer is exposed by carefully peeling it off with tweezers. The surface is sputtered to prevent charge buildup during subsequent measurements. From the surface, REM photographs (secondary electron detectors) with a magnification of 2000x and a resolution of 1024 to 768 pixels are recorded at 40 different measurement locations (statistical distribution, where only measurement locations showing at least 30 mutually distinguishable and focused fibers are considered).
[0106] The relative frequency of fiber diameters is determined by laying two auxiliary diagonals on each captured image, starting from the image corner (Bildecken). Only the fiber diameters of polypropylene fibers intersecting at least one of these auxiliary diagonals are considered. Fiber diameters are measured at the intersections with the auxiliary diagonals. If a polypropylene fiber intersects both diagonals or intersects multiple times, only one value is considered in each case. First, the total number of determined fiber diameters is determined. This corresponds to the number of all polypropylene fibers intersecting at least one of the two diagonals (reference number). From the total number of determined fiber diameters (reference number), in the next step, the number of fiber diameters in the range of 400 nm to 600 nm and the number of fiber diameters in the range of >600 nm to 800 nm are determined. The quotient of the number of fiber diameters in the corresponding region and the total number of determined fiber diameters is multiplied by 100 to obtain the relative frequency [%] of that fiber diameter. An average of the results for the studied image photographs is then formed.
[0107] Melt Flow Rate (MFR)
[0108] First, a polypropylene melt was prepared by melting metallocene-catalyzed PP (MFR 1800 g / 10 min, measured using ISO 1133-1). The heated sample was loaded with a weight of 2.16 kg at 230 °C, and the outflow was determined over a period of 10 minutes.
[0109] List of reference numerals
[0110] 1 First substrate
[0111] 2 First layer
[0112] 3 Second layer
[0113] 5 Second substrate
[0114] 10 Filter Material
Claims
1. A filter material (10) comprising a first layer (2) containing meltblown polypropylene fibers having a fiber diameter in the range of 400 nm to 600 nm at a relative frequency of at least 20%, for example, 20% to 60%, as determined by means of the method disclosed in the specification, and having a fiber diameter in the range of >600 nm to 800 nm at a relative frequency of at least 20%, for example, 20% to 60%, as determined by means of the method disclosed in the specification.
2. The filter material (10) according to claim 1, wherein the first layer (2) is composed of meltblown polypropylene fibers with a fiber diameter of less than 5 μm, wherein the polypropylene fibers have a fiber diameter in the range of 400 nm to 600 nm at a relative frequency of 20% to 60% as determined by means of the method disclosed in the specification, and have a fiber diameter in the range of >600 nm to 800 nm at a relative frequency of 20% to 60% as determined by means of the method disclosed in the specification.
3. The filter material (10) according to claim 1 or 2, wherein the first layer (2) has a layer thickness in the range of 10 μm to 200 μm, preferably 20 μm to 150 μm and particularly 40 μm to 80 μm.
4. The filter material (10) according to any one of the preceding claims, wherein the filter material further comprises a first substrate (1), wherein the first layer (2) is disposed on the first substrate (1), and wherein, In particular, polypropylene fibers are deposited on the first substrate (1), wherein the first substrate (1) is selected from at least one of spunbond nonwoven fabric, wet nonwoven fabric, short fiber nonwoven fabric, loose fabric, knitted fabric, woven fabric, braided fabric and combinations thereof.
5. The filter material (10) according to any one of the preceding claims, wherein the filter material (10) has a layer thickness in the range of 60 to 600 μm, preferably 100 to 400 μm and particularly 200 to 300 μm.
6. The filter material (10) according to any one of the preceding claims, wherein the filter material further comprises a second layer (3) containing activated carbon, wherein the second layer (3) is preferably disposed on the first layer (2).
7. The filter material (10) according to claim 6, wherein the filter material (10) comprises a second substrate (5) and the second layer (3) is disposed on the second substrate (5), wherein the second substrate (5) is selected from at least one of spunbond nonwoven fabric, wet-laid nonwoven fabric, short fiber nonwoven fabric, loose fabric, knitted fabric, woven fabric, braided fabric and combinations thereof.
8. The filter material (10) according to claim 7, wherein the second substrate (5) has a layer thickness in the range of 200 to 800 μm, particularly 450 to 600 μm.
9. The filter material (10) according to any one of claims 6 to 8, wherein the activated carbon has a sieve size of 20×50 mesh to 60×150 mesh and particularly 30×60 mesh to 60×120 mesh.
10. The filter material (10) according to any one of claims 6 to 9, wherein the second layer (3) comprises a hot melt adhesive bonding line (4), wherein the hot melt adhesive bonding line (4) and the activated carbon are jointly applied to the second substrate, wherein the material of the hot melt adhesive bonding line is preferably at least one polyolefin, particularly polypropylene.
11. The filter material (10) according to any one of claims 7 to 9, wherein the filter material comprises the following layer arrangement: a first substrate (1) / a first layer (2) / a second layer (3) / a second substrate (5), wherein the filter material (10) has a layer thickness in the range of 500 to 2500 μm, more preferably 800 to 2000 μm, and particularly 1500 to 1800 μm.
12. An air filter, water filter or particulate filter, comprising the filter material (10) according to any one of the preceding claims.
13. A method for preparing filter material (10), preferably a method for preparing filter material (10) according to one or more of claims 3 to 11, the method comprising the following steps: - Prepare polypropylene melt, wherein the melt flow rate (MFR) of polypropylene is 800 to 4000 g / 10 min, particularly 1100 to 2800 g / 10 min. - Adding at least one sterically hindered hydroxylamine ester, thereby obtaining a meltblown mixture in which the content of the sterically hindered hydroxylamine ester is in the range of 0.1 to 5% by mass, preferably 0.1 to 3% by mass, and particularly 0.1 to 2.5% by mass, based on the total weight of the meltblown mixture. - The meltblown mixture is meltblown under tension with air at a temperature of at least 240°C, for example, 240°C to 300°C, measured at the nozzle, to obtain meltblown polypropylene fibers preferably having a fiber diameter of less than 1 μm, wherein the polypropylene fibers have a fiber diameter in the range of 400 nm to 600 nm at a relative frequency of at least 20%, for example, 20% to 60%, as determined by the method disclosed in the specification, and have a fiber diameter in the range of >600 nm to 800 nm at a relative frequency of at least 20%, for example, 20% to 60%, as determined by the method disclosed in the specification. - Polypropylene fibers prepared by spinning are laid on a first substrate (1) to prepare a polypropylene filter sheet.
14. The method of claim 13, wherein the method further comprises the following steps: - Preparation of activated carbon filter sheets, comprising: Activated carbon is applied to the second substrate (5). The hot melt adhesive bonding line (4) is laid on the activated carbon, and - The activated carbon filter sheet is connected to the polypropylene filter sheet to obtain the following layer arrangement: second substrate (5) / activated carbon filter sheet = second layer (3) and hot melt adhesive bonding line (4) / polypropylene filter sheet = first layer (2) / first substrate (1).
15. Application of meltblown polypropylene fibers as filter material sheets, wherein the meltblown polypropylene fibers preferably have a fiber diameter of less than 1 μm, wherein the polypropylene fibers have a fiber diameter in the range of 400 nm to 600 nm at a relative frequency of at least 20%, for example, 20% to 60%, as determined by means of the methods disclosed in the specification, and have a fiber diameter in the range of >600 nm to 800 nm at a relative frequency of at least 20%, for example, 20% to 60%, as determined by means of the methods disclosed in the specification.
Citation Information
Patent Citations
Non-woven mats by melt blowing
US3849241A
Composite filter media with multiple fiber structures including nanofibers
WO2019213107A1